Monopole antenna technique for determining moisture content in the Dioscorea hispida tubers - Zainuddin, Mohamad Faiz; Abbas, Zulkifly; Muhammad Hafizi, Mardiah Hafizah; Jusoh, Mohamad Ashry; Razali, Mohd Hudzari (Southern Cross Publishing, 2013)
This study demonstrates the determination of moisture content in D. hispida tuber using microwave technique. A network analyzer was used to measure the reflection coefficient of a monopole antenna inserted in D. hispida tuber at different percentage of moisture content. The actual moisture content of D. hispida tuber was determined using oven drying method. The reflection coefficient measurement was performed at operating frequency between 2 MHz and 4 GHz. The best operating frequency to model the relationship between the magnitude of reflection coefficient and moisture content in the D. hispida samples was found to be 0.8 GHz. The model based on measured data of sample D with a regression value of 0.9399 and1.71% error was the most accurate model to predict moisture content in D. hispida tuber.